2006
DOI: 10.1016/j.soilbio.2006.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Fungal/bacterial ratios in grasslands with contrasting nitrogen management

Abstract: It is frequently hypothesised that high soil fungal/bacterial ratios are indicative for more sustainable agricultural systems. Increased F =B ratios have been reported in extensively managed grasslands. To determine the shifts in fungal/bacterial biomass ratio as influenced by grassland management and to find relations with nitrogen leaching potential, we sampled a two-year-old field experiment at an organic experimental farm in the eastern part of The Netherlands. The effect of crop (grass and grass-clover), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
256
3
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(300 citation statements)
references
References 70 publications
34
256
3
7
Order By: Relevance
“…Other studies also have reported a higher microbial activity Hole et al, 2005), which we did not find in our study. We did not find differences in fungal biomass, in contrast with some previous results (Yeates et al, 1997;de Vries et al, 2006), but in line with others (Shannon et al, 2002). These results might be due to the fact that added organic amendments in organic farming are generally easily degradable and therefore enhance mainly bacterial biomass and activity (Hole et al, 2005).…”
Section: Soil Food Web Structuresupporting
confidence: 84%
“…Other studies also have reported a higher microbial activity Hole et al, 2005), which we did not find in our study. We did not find differences in fungal biomass, in contrast with some previous results (Yeates et al, 1997;de Vries et al, 2006), but in line with others (Shannon et al, 2002). These results might be due to the fact that added organic amendments in organic farming are generally easily degradable and therefore enhance mainly bacterial biomass and activity (Hole et al, 2005).…”
Section: Soil Food Web Structuresupporting
confidence: 84%
“…This is higher than with other studies showing that fungi and fungal-feeding organisms are often reduced when soil N fertility and recycling increases (Coleman et al 1983;Bardgett et al 1999;De Vries et al 2006, 2007Lauber et al 2008;Krumins et al 2009). The mechanism is unknown but both are direct effects of fertilizer itself, and changes in the plant community and litter associated with fertilizers could be involved (Donnison et al 2000;Manning et al 2006).…”
Section: Discussioncontrasting
confidence: 55%
“…Fungi and bacteria are known to respond fast to increasing organic input [11,31]. During nun moth outbreaks in pine forests, the N input via throughfall was 24% higher and 300% higher via feces and needle litter on defoliated sites during the vegetation period [25].…”
Section: The Soil Fungal and Bacterial Population Size Responds To Inmentioning
confidence: 99%